The Dominion Housing Act - Belec, John (Urban History Review / Revue d'histoire urbaine, 1997)
Since its inception fifty years ago, Canada Mortgage and Housing Corporation has played a dominant role in the development of Canadian housing. Although the policy mechanisms and directions have expanded over the years, the primary role of CMHC has remained consistent since 1946; to promote home ownership by reducing the risk inherent in mortgage loans, to financial institutions. This policy predates CMHQ in 1935 the Dominion Housing Act (DHA) initiated joint lending on mortgages between lenders and the federal government The joint-lending arrangement continued with the National Housing Act in 1938 and responsibility for its administration was inherited by CMHC A basic shift in policy occurred in 1954 when joint lending was replaced with the current programme of mortgage insurance.Although state-assisted mortgage policy is often cited to have been central to the building of the post-war suburb in Canada, empirical analysis is lacking. This paper analyses the socio-spatial impact of the DHA through use of original mortgage files. DHA-sponsored mortgage lending featured pronounced class and geographical biases. Although a suburban orientation was present from the beginning, the middle classes were generally unable to participate.